Pengaruh Media Sosial terhadap Minat Berwirausaha pada Gen Z - Tiara Dara Pratiwi; Alinda Nuraini; Santiani Tri Widiawati; Sri Mulyeni (Jurnal Riset dan Inovasi Manajemen, 2026)
This research focuses on the use of social media among Gen Z students at the Faculty of Economics, Universitas Nasional Pasim, specifically in their first semester, with the primary obejctive of identifying the impact of social media usage on entrepreneurial interest Gen Z. Utilizing a quantitative method with a population of 94 individuals and a sample derived using a 5% margin, data were collected through questionnaires. The analytical results through validityand reliability tests confirmed that all data were both valid and reliable, while the simple regression analysis indicated that the regression model is feasible and relevant. This is evidenced by an R-Square value os 0.575, showing that 57,5% of the variation in entrepreneurial interest is influenced by social media usage, while the remaining 42.5% is affected by external factors. Furthermore, the F-count of 19.580 exceeds the F-table of 3.10, proving that social media usage significantly impacts entrepreneurial interest for instance, platforms like TikTok serve not only as entertainment but also as vital tools for information, business learning, and promotion. Such platforms encourage students to develop the courage to build businesses and foster independence, creativity, risk taking and readiness to create jobs and face future economic challenges. Ultimately, utilizing social media in a positive and productive manner serves as an effective strategy for cultivating the entrepreneurial spirit an dinterest among Gen Z.